Synthesis and antifungal activity of C-21 steroids with an aromatic D ring - Sonego, Juan Manuel (2013)
Six analogues of salpichrolides with a simpliﬁed side chain (6?11) were synthesized using a new methodology to obtain steroids with an aromatic D-ring. The key step was the elimination of HBr in a vicinal dibromo D-homosteroid by treatment with 1,4-diazabicyclo[2.2.2]octane (DABCO). All new compounds were completely characterized by 2D NMR techniques and tested on two fungal pathogenic species, Fusarium virguliforme and Fusarium solani.